New-onset lupus nephritis associated with COVID-19 infection. (July 2022) - Kazzi, Brigitte; Fine, Derek; Geetha, Duvuru; Chung, Melody; Monroy-Trujillo, Manny; Timlin, Homa
A dysregulated immune response plays a critical role in systemic lupus erythematosus (SLE) pathogenesis. Environmental factors such as viruses, including coronavirus 2 (COVID-19), have been described to play a role in SLE presentation and exacerbation. These viruses trigger a host's humoral and cellular immunities typically essential in elimination of the viral infection. We present a case of a Hispanic male who developed new-onset lupus nephritis class II after a COVID-19 infection.